The biomechanical characteristics of high-performance endurance running - Preece, S. J.; Bramah, C.; Mason, D. (European Journal of Sport Science, 2019)
The biomechanical profile of high-level endurance runners may represent a useful model that could be used for developing training programmes designed to improve running style. This study, therefore, sought to compare the biomechanical characteristics of high-performance and recreational runners. Kinematic and kinetic measurements were taken during overground running from a cohort of 14 high-performance (8 male) and 14 recreational (8 male) runners, at four speeds ranging from 3.3 to 5.6 m s-1. Two-way ANOVA analysis was then used to explore group and speed effects and principal component analysis used to explore the interdependence of the tested variables. The data showed the high-performance runners to have a gait style characterised by an increased vertical velocity of the centre of mass and a flight time that was 11% longer than the recreational group. The high-performance group were also observed to adopt a forefoot strike pattern, to contact the ground with their foot closer to their body and to have a larger ankle moment. Importantly, although observed group differences were mostly independent of speed, the tested variables showed a high degree of interdependence suggesting an underlying unitary phenomenon. This is the first study to compare high-performance and recreational runners across a full range of kinematic and kinetic variables. The results suggest that high-performance runners maintain stride length with a prolonged aerial phase, rather than by landing with a more extended knee. These findings motivate future intervention studies that should investigate whether recreational runners could benefit from instruction to decrease shank inclination at foot contact.